Effects of three types of resisted sprint training devices on the kinematics of sprinting at maximum velocity - Alcaraz, P. E.; Palao, J. M.; Elvira, J. L. L.; Linthorne, N. (The Journal of Strength and Conditioning Research, 2008)
Resisted sprint running is a common training method for improving sprint-specific strength. For maximum specificity of training, the athlete's movement patterns during the training exercise should closely resemble those used when performing the sport. The purpose of this study was to compare the kinematics of sprinting at maximum velocity to the kinematics of sprinting when using three of types of resisted sprint training devices (sled, parachute, and weight belt). Eleven men and 7 women participated in the study. Flying sprints greater than 30 m were recorded by video and digitized with the use of biomechanical analysis software. The test conditions were compared using a 2-way analysis of variance with a post-hoc Tukey test of honestly significant differences. We found that the 3 types of resisted sprint training devices are appropriate devices for training the maximum velocity phase in sprinting. These devices exerted a substantial overload on the athlete, as indicated by reductions in stride length and running velocity, but induced only minor changes in the athlete's running technique. When training with resisted sprint training devices, the coach should use a high resistance so that the athlete experiences a large training stimulus, but not so high that the device induces substantial changes in sprinting technique. We recommend using a video overlay system to visually compare the movement patterns of the athlete in unloaded sprinting to sprinting with the training device. In particular, the coach should look for changes in the athlete's forward lean and changes in the angles of the support leg during the ground contact phase of the stride.